Analysis of the Management of the Integrated Non-Communicable Disease Control Program (Posbindu-PTM) in the Working Area of Rawasari Public Health Center in 2024 - Gresela Yulya Br.Tanggang; Arnild Augina; Rizalia Wardiah; Adila Solida; Silvia Mawarti Perdana (Jurnal Ilmu Kedokteran dan Kesehatan Indonesia, 2025)
Non-Communicable Diseases (NCDs) have become a significant health issue requiring serious attention. Data from the Jambi City Health Office shows an increase in NCD cases from 16,154 in 2022 to 16,246 in 2023, with 4,129 cases being the highest. This study aims to analyze the management of the integrated NCD control post (Posbindu) at Rawasari Community Health Center. Using a qualitative research method with a descriptive-analytical approach, the study involved 11 informants, including healthcare workers and Posbindu cadres. Data were collected through interviews, observations, and document reviews. The findings indicate that program planning is not yet optimal due to a lack of cadres and inadequate facilities and infrastructure. Task organization is functioning as expected, but the limited number of cadres forces healthcare workers to provide additional assistance. The program is implemented through socialization efforts, but the five-stage system is not fully standardized, and community participation remains low. Monitoring, recording, and reporting are in accordance with the 2019 Ministry of Health guidelines. Overall, the Posbindu NCD program at Rawasari Community Health Center is running fairly well, but challenges persist in planning and implementation. Improvements are needed, particularly in increasing the number of trained cadres, collaborating with relevant stakeholders, and optimizing the five-stage Posbindu service system to enhance program effectiveness.